PENGARUH KUALITAS PRODUK, HARGA, DAN GETOK TULAR TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA TOKO PD. PESAGI JAYA TANI DI SEKINCAU LAMPUNG BARAT - Gumelar A., Deny Sekti; Adhilla, Fitroh (Jurnal Fokus Manajemen Bisnis, 2018)
This study aims to analyze the effect of product quality, prices, and infectiousness to the purchasing decision at PD Pesagi jaya farmers in West Lampung Sekincau. In this study the population used is a customer who once bought at a PD Pesagi glorious farmer. Based on the results of questionnaire data analysis of 60 customer respondents who once bought at a PD Pesagi glorious farmer using techniques non probability sampling which is a technique that does not provide opportunities or equal opportunity for each element or member of the population to be elected be sampled using purposive sampling, test instruments use validity and reliability test analysis, analysis tools with using multiple regression, hypothesis testing through t test and F test, as well as analysis of the coefficient of determination (R2). Hypothesis testing using the t test shows that three variables independent studied are the variables of product quality, price, and infectiousness proven to have a positive and significant effect on the dependent variable, i.e buying decision. Then through the F test can be seen that the third independent variables are feasible to test the dependent variable decision the purchase.